Ammonia gas sensor based on layered MoTe2 and TiO2 heterojunction, preparation process and application
By using liquid phase peeling and hydrothermal method in an ammonia sensor of MoTe2/TiO2 heterojunction composite material, MoTe2/TiO2 heterojunction composite nanomaterials are prepared by liquid phase peeling and hydrothermal methods, the problems of low response, slow recovery and poor selectivity in the prior art ammonia sensors at room temperature are solved, and the ammonia detection effect with high sensitivity, rapid recovery and low detection lower limit is achieved.
Patent Information
- Application Number
- CN202510142451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing ammonia sensors based on metal oxide semiconductor materials have problems such as low response, slow recovery and poor selectivity at room temperature, which limits their application scenarios.
An ammonia gas sensor based on layered MoTe2 and TiO2 heterojunction was used to prepare MoTe2/TiO2 heterojunction composite nanomaterials by liquid phase peeling and hydrothermal method to form gas-sensitive materials on the interdigital electrode plate to achieve high sensitivity and rapid recovery at room temperature.
It achieves high sensitivity, selectivity, rapid recovery and detection lower limits to ppb level for ammonia at room temperature, greatly improving the performance of the sensor.
Smart Images

Figure CN119804577A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic components and relates to an ammonia gas sensor based on a layered MoTe2 and TiO2 heterojunction, a preparation process and an application thereof. Background Art
[0002] Ammonia (NH3) is a widely used chemical in various fields such as chemical industry, industrial manufacturing, and agricultural production. Ammonia is also one of the sources of air pollution. It is a toxic and harmful gas to the human body. Human contact with ammonia will irritate the human respiratory tract and eyes. When the concentration of ammonia is too high, it will cause permanent damage to the human respiratory system or even death. In addition, ammonia is also used as a biomarker to detect certain diseases. For example, the exhaled breath of patients with kidney disease contains a high concentration of ammonia exceeding 1.5ppm, while the concentration of ammonia in the exhaled breath of healthy people is about 0.83ppm. Ammonia with a concentration below 5ppm is usually not directly detected by the human nose, which is not conducive to the early detection of diseases. Therefore, the detection of sub-ppm concentration ammonia is crucial in various fields such as industry, medical care, indoor air quality supervision and environmental monitoring.
[0003] At present, ammonia sensors based on metal oxide semiconductor materials are the most widely used for ammonia detection, and have always attracted much attention due to their excellent gas-sensing performance and low cost. However, semiconductor gas sensors based on metal oxide materials generally need to work at higher temperatures (above 200°C) to increase the activation energy of gas adsorption and chemical reactions to achieve the purpose of enhancing gas-sensitive response and recovery performance. At room temperature, ammonia sensors based on metal oxide materials generally have problems such as low response, slow recovery and poor selectivity, which greatly limits their application scenarios.
[0004] In recent years, transition metal sulfide (TMDs) materials have become a research hotspot in the field of room temperature gas sensing because of their unique two-dimensional layered structure and adjustable physical and chemical properties with the number of layers. Among them, molybdenum ditelluride (MoTe2), as a member of TMDs, has a narrow bandgap and higher carrier mobility. These excellent properties make it promising to become a new type of gas-sensitive material. (Zhihong Feng, Yuan Xie, Jiancui Chen, et al. Highly sensitive MoTe2 chemical sensor with fast recovery rate through gate biasing, 2D Mater. 4 (2017) 25018) et al. studied the ammonia gas-sensing performance of molybdenum ditelluride FET sensors and found that under the optimal gate bias, MoTe2 sensors showed good sensitivity and recoverability to ammonia at room temperature, which makes MoTe2 promising to become an ammonia detector under room temperature conditions. Despite this, gas sensors based on pure MoTe2 materials still have problems with sensitivity and recovery.
[0005] Heterojunctions have been shown to be an effective way to control the sensing properties of two-dimensional materials, by creating close electrical contact at the interface between two different semiconductor materials, which has a huge impact on the performance of the sensor to improve the sensitivity and selectivity of gas sensors. In recent years, n-type wide-bandgap metal oxide semiconductor material TiO2 nanostructures have been widely used in the field of gas sensing due to their excellent physical and chemical properties and high activity, and the gas sensing properties of two-dimensional materials to ammonia can be effectively improved by introducing TiO2 into two-dimensional materials to form heterojunctions. For example, (Ziyu Qin, Chao Ouyang, Jian Zhang, et al. 2D WS2 nanosheets with TiO2 quantum dots decoration for high-performance ammonia gas sensing at room temperature, Sensors and Actuators B: Chemical 253 (2017) 1034-1042.) et al. used different proportions of TiO2 quantum dots to modify WS2 nanosheets to prepare pn heterojunction composite materials. The sensitivity of the sensor to 250ppm ammonia at room temperature was nearly 17 times higher than that of single-component WS2, and the stability of the WS2 sensor was improved, showing good ammonia sensitivity at room temperature.
[0006] Based on the above situation, we proposed an ammonia sensor based on MoTe2 / TiO2 pn heterojunction composite material, and tested the microstructure of the composite material and the gas sensing performance of the sensor at room temperature. The experimental results show that the sensor has high sensitivity, selectivity, fast recovery and a detection limit as low as ppb level for ammonia at room temperature, and has potential practical application value.
[0007] Therefore, the present invention aims to provide a high-performance ammonia gas sensor based on MoTe2 / TiO2 heterojunction nanocomposite material, in order to play an important role in the fields of environmental monitoring, industrial safety and public health. Summary of the invention
[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an ammonia gas sensor and a detection method thereof that can operate stably at room temperature and has good selectivity, high sensitivity and a low detection limit, thereby making it possible to realize a low-power portable ammonia gas sensing device.
[0009] The technical solution of the present invention:
[0010] An ammonia gas sensor based on layered MoTe2 and TiO2 heterojunction mainly consists of a gas-sensitive material and an interdigital electrode plate. The gas-sensitive material is coated on the surface of the interdigital electrode plate with a coating thickness of 40 μm to 80 μm. The gas-sensitive material is composed of a heterojunction composite nanomaterial of molybdenum ditelluride and titanium dioxide.
[0011] The preparation process of the molybdenum ditelluride and titanium dioxide heterojunction composite nanomaterial is as follows: liquid phase exfoliation treatment is performed on molybdenum ditelluride to obtain layered molybdenum ditelluride, and titanium dioxide nanoparticles are attached to the surface of the layered molybdenum ditelluride by a hydrothermal method.
[0012] The interdigital electrode plate is an alumina substrate with a pure gold electrode on the front side, with 8 pairs of interdigital pairs, a distance between interdigital electrodes of 0.18 mm, a thickness of 2 to 5 μm, a length and width of 13.4 mm and 7 mm respectively, and a heating electrode plate attached to the back side.
[0013] The working environment temperature of the ammonia gas sensor is room temperature.
[0014] A preparation process of an ammonia gas sensor based on a layered MoTe2 and TiO2 heterojunction comprises the following steps:
[0015] Step 1: Preparation of liquid-phase exfoliated MoTe2 powder;
[0016] (1) Grinding MoTe2 powder to a particle size less than 5 μm;
[0017] (2) placing the ground MoTe2 powder into a mixture of N-methylpyrrolidone and deionized water, and subjecting the mixture to ultrasonic dispersion treatment for 6 h in an ice bath to obtain a suspension; wherein the volume ratio of N-methylpyrrolidone to deionized water is 4:1, and the concentration of the MoTe2 powder in the mixture is 0.0142 mol / L;
[0018] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain a layered MoTe2 powder after liquid phase exfoliation;
[0019] Step 2: preparing layered MoTe2 powder and TiO2 heterojunction nanocomposite materials;
[0020] (1) grinding the exfoliated layered MoTe2 powder to a particle size of less than 3 μm, then placing it in deionized water for ultrasonic treatment for 1 h and magnetic stirring for 10 min to form a uniform suspension; wherein the concentration of the layered MoTe2 powder in the suspension is 0.0012 mol / L;
[0021] (2) adding a 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (1), and then magnetically stirring for 1 h to obtain a mixed solution; controlling the molar ratio of MoTe2 to TiF4 to be 4:1-8:1;
[0022] (3) The mixed solution obtained in step (2) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour; the product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the obtained solid product is washed with deionized water for multiple times, and the obtained solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial.
[0023] The operating temperature of the ammonia gas sensor based on MoTe2 / TiO2 heterojunction nanocomposite is room temperature.
[0024] Working principle of the present invention:
[0025] The ammonia gas sensor of the present invention is a resistive semiconductor gas sensor. For the resistive gas sensor, the detection of the target gas is based on the detection of the resistance change caused by the adsorption and desorption of the gas on the surface of the sensitive material. The electron transfer generated by the redox reaction of ammonia on the surface of the sensing material leads to the change of the resistance of the semiconductor material, which is the main mechanism for achieving detection. The real-time monitoring signal of the sensor is the change of the sensor resistance value.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention adopts liquid phase exfoliation combined with a hydrothermal method to obtain a novel heterojunction nanocomposite material. The raw materials are easy to obtain, low in price, and the heterojunction preparation process is simple. It is a two-dimensional semiconductor heterojunction preparation solution with small equipment investment and simple process flow.
[0028] (2) The heterojunction nanocomposite material prepared by the present invention has TiO2 nanoparticles uniformly attached to the surface of the flaky MoTe2. Due to liquid phase exfoliation and the introduction of TiO2, the stacking of MoTe2 is improved, and the material has a larger surface area. At the same time, the presence of a large number of nano-scale MoTe2 / TiO2 heterojunctions can promote the adsorption of gas on the surface of the sensitive material, promote the occurrence of redox reactions, and improve the efficiency of electron transfer between the gas and the sensitive material, thereby having excellent gas sensing performance at room temperature.
[0029] (3) The present invention has good selectivity and stable gas-sensing performance for ammonia, has a detection limit as low as ppb, and greatly reduces the recovery time of the sensor. In addition, the temperature required for the sensor to work is reduced, and it can work at room temperature, slowing down the aging and damage of the material caused by working in a higher temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope microscopic morphology image of the MoTe2 / TiO2 nanocomposite material of the present invention.
[0031] Figure 2 The resistance change curves of the MoTe2 / TiO2 nanocomposite gas sensor with different ratios at room temperature for 30 ppm ammonia.
[0032] Figure 3 This is a comparison chart of the response values and response / recovery time of the MoTe2 / TiO2 nanocomposite gas sensor with different ratios to 30 ppm ammonia at room temperature.
[0033] Figure 4 The response curves of single-component MoTe2 and MoTe2 / TiO2 nanocomposite sensors to 0.5-30 ppm ammonia at room temperature.
[0034] Figure 5 The response value and baseline resistance of MoTe2 / TiO2 nanocomposite gas sensor to 30ppm ammonia at different temperatures.
[0035] Figure 6 These are the response values of the MoTe2 / TiO2 nanocomposite gas sensor to seven gases at 30 ppm at room temperature. DETAILED DESCRIPTION
[0036] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0037] Example 1
[0038] (1) Weigh 50 mg of MoTe2 powder and grind it in an agate mortar for 30 min;
[0039] (2) The ground MoTe2 powder was placed in a mixture of 8 ml of N-methylpyrrolidone and 2 ml of deionized water and subjected to ultrasonic dispersion treatment in an ice bath for 6 h;
[0040] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain MoTe2 powder after liquid phase exfoliation;
[0041] (4) 21 mg of the liquid-phase exfoliated MoTe2 powder was placed in an agate mortar and ground for 10 min, then placed in 50 ml of deionized water for ultrasonic treatment for 1 h and magnetically stirred for 10 min to form a uniform suspension;
[0042] (5) adding 750 μL of 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (4), and then magnetically stirring for 1 h to obtain a mixed solution;
[0043] (6) The mixed solution obtained in step (5) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene with a volume of 100 ml, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed with deionized water for multiple times. The solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial, wherein the molar ratio of MoTe2 to TiO2 is 4:1.
[0044] Example 2
[0045] (1) Weigh 50 mg of MoTe2 powder and grind it in an agate mortar for 30 min;
[0046] (2) The ground MoTe2 powder was placed in a mixture of 8 ml of N-methylpyrrolidone and 2 ml of deionized water and subjected to ultrasonic dispersion treatment in an ice bath for 6 h;
[0047] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain MoTe2 powder after liquid phase exfoliation;
[0048] (4) 21 mg of the liquid-phase exfoliated MoTe2 powder was placed in an agate mortar and ground for 10 min, then placed in 50 ml of deionized water for ultrasonic treatment for 1 h and magnetically stirred for 10 min to form a uniform suspension;
[0049] (5) adding 600 μL of 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (4), and then magnetically stirring for 1 h to obtain a mixed solution;
[0050] (6) The mixed solution obtained in step (5) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene with a volume of 100 ml, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed with deionized water for multiple times. The solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial, wherein the molar ratio of MoTe2 to TiO2 is 5:1.
[0051] Example 3
[0052] (1) Weigh 50 mg of MoTe2 powder and grind it in an agate mortar for 30 min;
[0053] (2) The ground MoTe2 powder was placed in a mixture of 8 ml of N-methylpyrrolidone and 2 ml of deionized water and subjected to ultrasonic dispersion treatment in an ice bath for 6 h;
[0054] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain MoTe2 powder after liquid phase exfoliation;
[0055] (4) 21 mg of the liquid-phase exfoliated MoTe2 powder was placed in an agate mortar and ground for 10 min, then placed in 50 ml of deionized water for ultrasonic treatment for 1 h and magnetically stirred for 10 min to form a uniform suspension;
[0056] (5) adding 500 μL of 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (4), and then magnetically stirring for 1 h to obtain a mixed solution;
[0057] (6) The mixed solution obtained in step (5) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene with a volume of 100 ml, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed with deionized water for multiple times. The solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial, wherein the molar ratio of MoTe2 to TiO2 is 6:1.
[0058] Figure 1 The scanning electron microscope microscopic morphology of the layered MoTe2 / TiO2 composite nanomaterial prepared in Example 3 is given.
[0059] Example 4
[0060] (1) Weigh 50 mg of MoTe2 powder and grind it in an agate mortar for 30 min;
[0061] (2) The ground MoTe2 powder was placed in a mixture of 8 ml of N-methylpyrrolidone and 2 ml of deionized water and subjected to ultrasonic dispersion treatment in an ice bath for 6 h;
[0062] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain MoTe2 powder after liquid phase exfoliation;
[0063] (4) 21 mg of the liquid-phase exfoliated MoTe2 powder was placed in an agate mortar and ground for 10 min, then placed in 50 ml of deionized water for ultrasonic treatment for 1 h and magnetically stirred for 10 min to form a uniform suspension;
[0064] (5) adding 428 μL of 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (4), and then magnetically stirring for 1 h to obtain a mixed solution;
[0065] (6) The mixed solution obtained in step (5) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene with a volume of 100 ml, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed with deionized water for multiple times. The solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial, wherein the molar ratio of MoTe2 to TiO2 is 7:1.
[0066] Example 5
[0067] (1) Weigh 50 mg of MoTe2 powder and grind it in an agate mortar for 30 min;
[0068] (2) The ground MoTe2 powder was placed in a mixture of 8 ml of N-methylpyrrolidone and 2 ml of deionized water and subjected to ultrasonic dispersion treatment in an ice bath for 6 h;
[0069] (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain MoTe2 powder after liquid phase exfoliation;
[0070] (4) 21 mg of the liquid-phase exfoliated MoTe2 powder was placed in an agate mortar and ground for 10 min, then placed in 50 ml of deionized water for ultrasonic treatment for 1 h and magnetically stirred for 10 min to form a uniform suspension;
[0071] (5) adding 375 μL of 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (4), and then magnetically stirring for 1 h to obtain a mixed solution;
[0072] (6) The mixed solution obtained in step (5) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene with a volume of 100 ml, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour. The product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the solid product is washed with deionized water for multiple times. The solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial, wherein the molar ratio of MoTe2 to TiO2 is 8:1.
Claims
1. An ammonia gas sensor based on a layered MoTe2 and TiO2 heterojunction, characterized in that: The ammonia gas sensor is mainly composed of a gas-sensitive material and an interdigital electrode plate. The gas-sensitive material is coated on the surface of the interdigital electrode plate with a coating thickness of 40 μm to 80 μm. The gas-sensitive material is composed of a heterojunction composite nanomaterial of molybdenum ditelluride and titanium dioxide.
2. The ammonia gas sensor according to claim 1, characterized in that: The preparation process of the molybdenum ditelluride and titanium dioxide heterojunction composite nanomaterial is as follows: liquid phase exfoliation treatment is performed on molybdenum ditelluride to obtain layered molybdenum ditelluride, and titanium dioxide nanoparticles are attached to the surface of the layered molybdenum ditelluride by a hydrothermal method.
3. The ammonia gas sensor according to claim 1, characterized in that: The interdigital electrode plate is an alumina substrate with a pure gold electrode on the front side, with 8 pairs of interdigital pairs, a distance between interdigital electrodes of 0.18 mm, a thickness of 2 to 5 μm, a length and width of 13.4 mm and 7 mm respectively, and a heating electrode plate attached to the back side.
4. A preparation process of an ammonia gas sensor based on a layered MoTe2 and TiO2 heterojunction, characterized in that: The following steps are involved: Step 1: Preparation of liquid-phase exfoliated MoTe2 powder; (1) Grinding MoTe2 powder to a particle size less than 5 μm; (2) placing the ground MoTe2 powder into a mixture of N-methylpyrrolidone and deionized water, and subjecting the mixture to ultrasonic dispersion treatment for 6 h in an ice bath to obtain a suspension; wherein the volume ratio of N-methylpyrrolidone to deionized water is 4:1, and the concentration of the MoTe2 powder in the mixture is 0.0142 mol / L; (3) The suspension obtained in step (2) was allowed to stand for 24 hours, and then the material was washed alternately with deionized water and ethanol for several times, and the precipitate was collected by centrifugation. Finally, the precipitate was dried at 60° C. for 12 hours to obtain a layered MoTe2 powder after liquid phase exfoliation; Step 2: preparing layered MoTe2 powder and TiO2 heterojunction nanocomposite materials; (1) grinding the exfoliated layered MoTe2 powder to a particle size of less than 3 μm, then placing it in deionized water for ultrasonic treatment for 1 h and magnetic stirring for 10 min to form a uniform suspension; wherein the concentration of the layered MoTe2 powder in the suspension is 0.0012 mol / L; (2) adding a 0.02 mol / L TiF4 aqueous solution to the suspension obtained in step (1), and then magnetically stirring for 1 h to obtain a mixed solution; controlling the molar ratio of MoTe2 to TiF4 to be 4:1-8:1; (3) The mixed solution obtained in step (2) is transferred to a hydrothermal reactor lined with polytetrafluoroethylene, and a hydrothermal reaction is carried out at a temperature of 170° C. for 1 hour; the product after the hydrothermal reaction is separated into solid and liquid by a centrifuge, and the obtained solid product is washed with deionized water for multiple times, and the obtained solid product is placed in a drying oven and dried at 60° C. for 12 hours to obtain a MoTe2 and TiO2 heterojunction composite nanomaterial.
5. The operating temperature of the ammonia gas sensor based on layered MoTe2 and TiO2 heterojunction as described in claim 1 is room temperature.
Citation Information
Cited By
Ammonia gas sensor based on SnS2 and In2S3 heterojunction, preparation process and application
CN116297705A
An ammonia gas sensor based on SnS2 and In2S3 heterojunction, preparation process and application
CN116297705B
Layered MoTe2 and ZnO heterojunction-based gas sensor as well as preparation method and application thereof
CN117990748A
High-sensitivity fast-recovery ammonia gas sensor and preparation method thereof
CN120971517A
High-sensitivity fast-recovery ammonia sensor and preparation method thereof
CN120971517B